Show your rare, handle with care: a knowledge brokers network to handle rare disease patients. (13th November 2019) - Rubba, F; Alfano, R; Schiavone, D; Scamardo, M S; Landolfo, D; Barbieri, O; Carannante, I; D'Onofrio, G; Guida, A; Triassi, M
Abstract: Background: In Rare diseases patients. difficult in diagnosis can produce inappropriate pathways of care. A correct diagnosis took almost 5 years in Europe and 7.3-7.6 y in US. The directive 2011/24/EU provides a legal regulatory asset for the European Reference Networks (ERNs). ERNs are designed to connect health care providers and centers of expertise for gaining appropriate pathways of high-quality care and to support sponsorship in order to make healthcare closer to the patients. Federico II University actually has 9 confirmed ERNs. Methods: We connected the patient related activities inside the ERNs and we planned a project-based network that creates harmonization of diagnostic tools and widespread diffusion of screening activity able to drive diagnostic enrichment. The Hospital Chief Office together with the Public Health Department acts as "Knowledge brokers" (KB) defined as connectors who may crisscross the hierarchical boundaries. We scheduled interventions into the ERNs and future improvements. Interventions areas have been represented in a conceptual map. Results: Brokers into the network are attended to allow better merged innovation rate and sharing data. Improvements could be directed toward: 1) sharing data and communication, 2) diagnostic enrichment 3) hospital services networking into the path. Including this model in the regional pathways may build a common platform to support appropriate care in disease-endemic regions. The designed model finally aimed at define how humanization and networking of care can be measured as gain in efficiency along the overall path. Conclusions: Network potential may overload a simply specific hub focused approach. The "criss cross" knowledge brokering (could be a strategy able to support clinical and diagnostic activities. To proceed over, in orphan disease handling, we may progress from approaches centered on florid cases toward a balanced screening design, able to guarantee a diagnostic enrichment for a rare condition. Key messages: Implicit and formal Networking cam help rare disease handling. Sharing data and diagnostic enrichment are the main issues.